Preservice Elementary Teachers' Perceptions After Visiting an Interactive Science Center - David H. Palmer (Networks: An Online Journal for Teacher Research, 2002)
This paper reports an action research study involving preservice elementary teachers enrolled in a college science methods course (ie. the course focussed on how to teach science at elementary school). There was an interactive science center nearby which many local elementary classes regularly visited, so I decided to set my students the task of visiting the center and reporting on it. However, I was unsure as to what outcomes the students would gain from the experience. I therefore asked the students to each write a short passage explaining what they had learnt from the experience. According to their responses, the main benefit was that the visit reinforced the value of hands-on activities for teaching science and making it fun. Through the visit, the students also became aware of the center as a teaching resource, and developed ideas about the factors involved in organising an excursion.